Clinical characteristics of pulmonary cryptococcosis coexisting with lung adenocarcinoma: Three case reports - Zheng, Gui-Xian (World J Clin Cases, 2020)
BACKGROUND: Pulmonary cryptococcosis (PC) is an invasive fungal disease caused mainly by Cryptococcus (C.) neoformans or C. gattii. It may be present in immunocompetent or immunocompromised patients. The radiographic features of PC vary, and the most common computed tomography manifestation is the presence of solitary or multiple pulmonary nodules or masses distributed in the outer zone of the lung field. The appearance of nodular or mass-like PC on computed tomography scans resembles that of primary or metastatic lung cancers, and differential diagnosis is sometimes difficult. The coexistence of PC and malignant tumors is rarely observed. CASE SUMMARY: This paper reports three cases of PC combined with lung adenocarcinoma diagnosed by video-assisted thoracic surgery lung biopsy, which were successfully managed by early diagnosis and treatment. CONCLUSION: The present case report might serve as a reminder not to neglect PC coexisting with adenocarcinoma. Early diagnosis and treatment lead to a better prognosis.